TRANSFER OF GOVERNMENT AUTHORITY TO MANAGE MINERAL AND COAL MINING AFTER THE ENACTMENT OF OMNIBUS LAW - Ridho Ilahi, Muhammad Marfiliansyah; Ananda, Nesa; Amelia, Dina; Oktaviyanti, Putri; Auliya, Jessica (Communale Journal, 2024)
The significant reform in mining law in force in Indonesia is Law No. 3 of 2020 on Mineral and Coal (Minerba), which amends Law No. 4 of 2009, marks a new chapter in the transfer of authority from local and national governments to the Central Government. This study aims to analyze how local government jurisdiction over coal and minerals was transferred to the Central Government and how this affected the implementation of decentralization. Normative judicial research approaches are employed. This study's findings show that the Minerba Law amendment only gives authority to the Central Government, and coal and mineral mining agreements have become centralized. The local Governments only have delegated authority, which does not mean that local Governments have no control over managing coal and mineral mining at all; there is still authority to operate coal and mineral mining in the regions by following directions from the central government. The current mining legislation needs to support solid collaborations between central and local governments to promote sustainability in the future. Because local governments are better informed about mining situations in their regions, the central government must grant authority to control coal and mineral mining. Strict oversight is necessary to prevent local governments from abusing their authority.